Mechanisms of Steatosis-Derived Hepatocarcinogenesis: Lessons from HCV Core Gene Transgenic Mice. (December 2021) - Diao, Pan; Jia, Fangping; Wang, Xiaojing; Hu, Xiao; Kimura, Takefumi; Nakajima, Takero; Aoyama, Toshifumi; Moriya, Kyoji; Koike, Kazuhiko; Tanaka, Naoki
Abstract: Hepatitis C virus (HCV) is a major cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC) worldwide. Among the structural proteins of HCV, the HCV core protein has the ability to regulate gene transcription, lipid metabolism, cell proliferation, apoptosis, and autophagy, all of which are closely related to the development of HCC. Transgenic mice carrying the HCV core gene exhibited age-dependent insulin resistance, hepatic steatosis, and HCC that resembled the clinical characteristics of chronic hepatitis C patients. Several dietary modifications, including calorie restriction and diets rich in saturated fatty acids, trans fatty acids, or cholesterol, were found to influence hepatic steatogenesis and tumorigenesis in HCV core gene transgenic mice. These strategies modulated hepatocellular stress and proliferation, in addition to hepatic fibrotic processes and the microenvironment, thereby corroborating a close interconnection between dietary habits and steatosis-related hepatocarcinogenesis. In this review, we summarize the findings obtained from mouse models transgenic for the HCV genome, with a special focus on HCV core gene transgenic mice, and discuss the mechanisms of steatogenesis and hepatocarcinogenesis induced by the HCV core protein and the impact of dietary habits on steatosis-derived HCC development.